Corporate Social Responsibility and Firm Financial Performance: The Mediating Role of Firm Innovation - Ibrahim, Ibrahim; Makaryanawati, Makaryanawati; Juliardi, Dodik (International Journal of Business, Law, and Education, 2023)
This study aimed to determine the effect of Corporate Social Responsibility (CSR) on the financial performance of companies in the mining sector listed on the Indonesia Stock Exchange (IDX) in 2018-2021. It also aims to explore the role of corporate innovation as a mediating factor in the link between CSR and financial performance. The sampling technique in this study was purposive sampling. Path analysis is used as a data analysis technique in this study. The results of the study show that CSR has a positive effect on financial performance and firm innovation. In addition, firm innovation has a positive effect on financial performance. The results also support the partial mediating effect of firm innovation on the relationship between CSR and corporate financial performance. The findings of this study can increase stakeholder awareness of the importance of CSR. This is because CSR is proven to be one of the important drivers for companies to be more innovative and gain competitive advantage